Contrastive analysis, linguistics, and translation: rivals or allies? - Novakova, Eva (Bohemica Olomucensia, 2019)
The paper discusses principles of the contrastive functional analysis (CFA) and its practical application in translation. It ponders on the relationship between contrastive linguistics and translation studies, proposes a model of CFA and tests its potential and limits in translation criticism.
Keywords: contrastive functional analysis; translation; EU official documents; translation criticism